Analisi Kinerja Alat Crushing Plant Pada Penambangan Limestone di PT Semen Padang (Persero) Tbk, Bukit Karang Putih Indarung, Padang Sumatera Barat - Aidil Lian Jamirul; Nurul Aflah; Febi Mutia; Muchlis Muchlis (Journal of Geosciences, Mining Engineering, and Technology, 2022)
PT Semen Padang is a cement factory which uses limestone as the main raw material. This companny located in mining area of Bukit Karang Putih, Lubuk Kilangan Idarung district, Padang, West Sumatera. Currently, PT Semen Padang has 3 (three) units of the crushing plant for limestone crushing. Units of the crushing plant are The Limestone Crusher II, Limestone Crusher IIIA, and Limestone Crusher IIIB. The research aims to know the working system of crushing plant units and evaluate the performance of the crushing plant. Another purpose of this study is to analyze the size of limestone feed material, which goes into limestone crushing plan unit using Manual photography analysis method, as well as to assess the effectiveness of the crusher towards the production target. PT Semen Padang currently has a monthly production target of 555.505 tons/month. Based on the measurement of performance parameters, the Mechanical and Physical Availability, each unit of the crushing plant has been working quite well. However, based on the Use of Availability and Effective Utilization parameters the performance of each crushing plant is still considered bad. The results showed that the presence of the value of underperformance of crushing plant unit has no effect on the company’s planned target of 555.505 tons/month, it can even reach above the target: 625.412 tons/month. Keywords: crushing plant, limestone crusher, effective utilization, crusher, manual  photography, mechanical availability, physical availability, use of availability.